Addressing Misconceptions in Genetics Through Conceptual Change Strategies: An Empirical Study Of Secondary Schools in Delta State, Nigeria - Ewere, Chukwuka Rita (Indonesian Journal of Educational Studies, 2025)
This study evaluated the effectiveness of conceptual change strategies on genetics achievement among secondary school students in Delta State, Nigeria. A quasi-experimental design involved 160 students, divided into an experimental and a control group. The experimental group was taught using conceptual change strategies like Predict-Observe-Explain (POE) and collaborative learning, while the control group received traditional lecture-based instruction. The Genetics Conceptual Understanding Test (GCUT) was administered as a pretest and posttest. Analysis of the data using ANCOVA showed that students taught with conceptual change strategies achieved significantly higher posttest scores than those in the control group, even after adjusting for initial differences. The study concludes that conceptual change strategies are more effective than traditional methods for enhancing students' understanding of genetics. It is recommended that teachers and curriculum planners adopt these approaches to address misconceptions and improve learning outcomes in biology.